PENGARUH MACAM PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL DUA VARIETAS KEDELAI HITAM (Glycine soja (L.) Merrill) - Ika Dwi Meilawasih; Sumarmi Sumarmi; Kharis Triyono (Innofarm:Jurnal Inovasi Pertanian, 2022)
This study aims to determine the effect of different types of organic fertilizers on the growth and yield of two varieties of black soybean (Glycine soja (L.) Merril ). The black soybean varieties used were the Mallika variety and the Lumajang local variety. The research site is in the Research and Collection Gardens, Faculty of Agriculture, Slamet Riyadi University, Surakarta. The research was carried out from May 19, 2021 to August 10, 2021. The design used was a Completely Randomized Design (CRD) with two factors. The types of treatment were: Mallika variety without fertilizer (V1P0), Lumajang local variety without fertilizer (V2P0), Mallika variety with chicken manure (V1P1), Lumajang local variety with chicken manure (V2P1), Mallika variety with goat manure (V2P1). V1P2), local variety Lumajang with goat manure (V2P2), Mallika variety with cow manure (V1P3), local variety Lumajang with cow manure (V2P3), Mallika variety with guano fertilizer (V1P4), local variety Lumajang with guano fertilizer (V2P4). From these treatments, 9 types of treatment combinations and 1 control (without fertilizer) were obtained and were repeated 4 times so that 40 experimental units were obtained. Parameters observed included plant height, number of leaves, weight of wet stover, weight of dry stover, number of pods per plant, weight of pods per plant, number of seeds per plant, weight of dry seeds per plant, and weight of 100 seeds per plant. Data were analyzed using Analysis of Variance (Anova), if significantly different then the data was tested by Duncan's test at 5% level to distinguish the mean between treatments. The results showed that 1) The best treatment was obtained with the use of organic chicken manure, because the content of N,P,K in chicken manure was higher than other manures, and chicken manure had a fairly high nutrient content and decomposed relatively quickly. 2) The local variety Lumajang had more pods with an average of 75.25 in the treatment of chicken manure compared to the Mallika variety, this significantly affected the number of seeds in the Mallika variety less than the local Lumajang variety. The highest number of seeds in the local variety Lumajang was found in the cow manure treatment with an average of 142.50 seeds. 3) Mallika variety has large seed size, the highest average weight of 100 seeds is 43.23 g in chicken manure treatment.